A lower intensity of treatment may underlie the increased risk of thrombosis in young patients with masked polycythaemia vera. (16th August 2014) - Lussana, Federico; Carobbio, Alessandra; Randi, Maria L.; Elena, Chiara; Rumi, Elisa; Finazzi, Guido; Bertozzi, Irene; Pieri, Lisa; Ruggeri, Marco; Palandri, Francesca; Polverelli, Nicola; Elli, Elena; et al.
Summary In patients who do not meet the World Health Organization (WHO) criteria for overt polycythaemia vera (PV), a diagnosis of masked PV (mPV) can be determined. A fraction of mPV patients may display thrombocytosis, thus mimicking essential thrombocythaemia (ET). No previous studies have examined clinical outcomes of mPV among young JAK2‐mutated patients. We analysed a retrospective cohort of 538 JAK2‐mutated patients younger than 40 years, after a re‐assessment of the diagnosis according to the haemoglobin threshold for mPV. In this cohort of patients, 97 (18%) met the WHO criteria for PV, 66 patients (12%) were classified as mPV and 375 (70%) as JAK2‐mutated ET. Surprisingly, a significant difference in the incidence of thrombosis was found when comparing mPV versus overt PV patients (P = 0·04). In multivariate analysis, the only factor accounting for the difference in the risk of thrombosis was the less frequent use of phlebotomies and cytoreduction in mPV patients compared to those with overt PV. Thus, we emphasize the need for the identification of mPV in young JAK2‐mutated patients in order to optimize their treatments.